CeRu4Sn6, a strongly correlated material with nontrivial topology - Sundermann, Martin; Haverkort, Maurits W. (Arxiv, 2015)
Topological insulators form a novel state of matter that provides new opportunities to create unique quantum phenomena. While the materials used so far are based on semiconductors, recent theoretical studies predict that also strongly correlated systems can show non-trivial topological properties, thereby allowing even the emergence of surface phenomena that are not possible with topological band insulators. From a practical point of view, it is also expected that strong correlations will reduce the disturbing impact of defects or impurities, and at the same increase the Fermi velocities of the topological surface states. The challenge is now to discover such correlated materials. Here, using advanced x-ray spectroscopies in combination with band structure calculations, we infer that CeRu$_4$Sn$_6$ is a strongly correlated material with non-trivial topology.
Die Ziffern 4 und 6 im Titel sind tiefgestellt
Gesehen am 24.11.2017